Math tools, grades 3-12 : 64 ways to differentiate instruction and increase student engagement - Silver, Harvey F. 4 0 16; Brunsting, John R.,;Walsh, Terry; 5 (Thousand Oaks, California : Corwin Press, 2008)
Describes sixty-four teaching techniques for increasing student engagement in mathematics classroom environments, and discusses learning styles, how to choose the optimal tool to emphasize depending on the content, and also describes ways to use math tools--such as a memory box, word walls, and vocabulary organizers.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Study and teaching (Elementary);Study and teaching (Secondary);Study and teaching. -- Mathematics;Mathematics;Effective teaching;Learning strategies;Mathematics;Teaching;Learning and scholarship -- United States.;United States.;United States.;United States.;United States;United States.;United States; 20; 2